Traditional Beliefs and Practices in Masquerading: Effutu Context - Micah, Victor Kweku Bondzie; Donkor, Evans Kwadwo; Ankrah, Owusu-Ansah (Talenta Publisher, 2022)
The study elevates the masquerading culture of Effutu masquerade and examines its functionalism of the traditional beliefs and practices associated with the masquerading culture in Winneba, Central Region of Ghana. The study employed a descriptive research tool under the qualitative research approach through ethnographic inquiry, which aimed at collecting data to unearth these traditional beliefs and practices of the Effutu masquerade. The study used unstructured interviews, photographs, and direct observation as the form of instrumentations to elicit information from the federation, some members, and leaders of the various masquerade groups in Winneba. The data was analyzed using descriptive and interpretative phenomenological (IPA) analysis tools. It was revealed that the Effutu masquerade culture possessed traditional beliefs and practices that were shrouded in religious, socioeconomic and aesthetic contexts. Functionalism in Effutu masquerade culture was seen as a repository for a critical reflection of the visual culture that promotes Ghana’s tradition and cultural values. The study concludes that the Effutu masquerade, irrespective of its distrust, contains elements of cultural richness and important traditional values that demonstrate a degree of philosophical urgency.